저소득층의 자살생각에 영향을 미치는 요인 -강원도 자활근로사업 참여자를 중심으로 - 김정유; 이동하; 황정우; 이강욱; Kim, Jung-Yoo; Lee, Dong-Ha; Hwang, Jung-Woo; Lee, Kang-Uk (한국콘텐츠학회 논문지, 16(12), 2016)
Using 1,419 lower-income group participating self-sufficiency program in Gangwon Province, this study investigated what would affect suicidal ideation of low-income. For the purpose showed significant differences in suicide ideation, as living status, subjective economic status, family friends neighbors contact frequency, using social services, chronic disease or not, drinking frequency, depression, the suicide of a family or someone close, suicide attempt by setting the independent variables was performed logistic regression analysis. The results showed that neighbors contact frequency, depression, the suicide of a family or someone close, suicide attempts affect suicidal ideation. It was an unusual result in lower-income group participating self-sufficiency program do not appear as factors affecting suicidal ideation. Based on the findings, this study provides suggestions to prevent suicide of lower-income and future research agenda. 본 연구는 저소득층의 자살생각에 영향을 미치는 요인을 파악하고자 강원도 내에서 자활근로사업에 참여하고 있는 1,419명을 대상으로 한 설문 결과를 이용하였다. 이를 위하여 각 특성에 따른 자살생각의 차이에서 유의미한 차이를 보인 독거 여부, 주관적 경제상태, 가족 친구 이웃과의 연락빈도, 사회서비스 이용 여부, 만성질환 유무, 음주빈도, 우울 여부, 지인자살 여부, 자살시도 여부를 독립변수로 설정하여 로지스틱 회귀 분석을 실시하였다. 분석결과 이웃과의 연락빈도, 우울여부, 지인자살 여부, 자살시도 여부가 자살생각에 영향을 미치는 것으로 나타났다. 저소득층인 자활근로자에 대한 연구에서 주관적 경제상태가 자살생각에 영향을 미치는 요인으로 나타나지 않은 것이 특이한 결과였다. 연구결과를 기반으로 자살에 취약한 저소득층 대상 자살예방과 관련된 시사점과 향후 연구방향을 제안하였다.